Exploring the effect of animal captivity facility on domestic tourism in Tanzania - Bulenga, Busagwe; Batinoluho, Ladislaus (Journal of Tourism, Culinary, and Entrepreneurship (JTCE), 2025)
The effect of animal captivity facilities on domestic tourism is not well-established in Tanzania. Animal captivity facilities take part in an essential role in tourism by providing room for education, conservation, and recreation, while also contributing to the local economy, yet their impact on the domestic tourism sector has never been extensively studied. This study explores the effects of animal captivity facilities on domestic tourism in Tanzania. Using both quantitative and qualitative methodology, the study reveals that animal captivity facilities remain relevant and beneficial to domestic tourism, particularly in providing educational opportunities, entertainment, and conservation awareness. However, challenges such as high operational costs, limited promotional efforts, and ethical concerns regarding animal welfare affect their full potential. This study emphasizes the need for improved facility management, enhanced visitor experiences, ethical animal care practices, community engagement, and strategic marketing initiatives to attract more domestic tourists. Furthermore, the findings provide valuable understanding for policymakers, facility managers, and also different tourism stakeholders looking to optimize the task of animal captivity facilities in domestic tourism development.